Identification of a chemical modulator of EZH2-mediated silencing by cell-based high-throughput screening assay. (25th January 2019) - Murashima, Akihiro; Shinjo, Keiko; Katsushima, Keisuke; Onuki, Tetsuo; Kondoh, Yasumitsu; Osada, Hiroyuki; Kagaya, Noritaka; Shin-ya, Kazuo; Kimura, Hiroshi; Yoshida, Minoru; Murakami, Shingo; Kondo, Yutaka
Abstract: Dysregulation of enhancer of zeste homologue 2 (EZH2), a methyltransferase component of polycomb repressive complex 2, is found in many types of cancers especially those that are highly progressive and aggressive. Specific catalytic inhibitors of EZH2 have high anti-tumour activity, particularly in lymphomas with EZH2 activating mutations. However, the clinical benefits of EZH2 catalytic inhibitors in tumours overexpressing EZH2 are still limited. Here, we identified NPD13668, a novel modulator of EZH2-mediated gene silencing, from 329, 049 small chemical compounds using a cell-based high-throughput screening assay. NPD13668 reactivated the expression of silenced H3K27me3 target genes together with depletion of the H3K27me3 modification. In addition, NPD13668 repressed the cell growth of prostate cancer cell lines (PC3 and LNCaP) and ovarian cancer cell lines (SKOV3 and NIH-OVCAR3). NPD13668 partially inhibited the methyltransferase activity of EZH2 in vitro . Genome-wide expression analysis revealed that after NPD13668 treatment, about half of the upregulated genes overlapped with genes upregulated after treatment with GSK126, well-known EZH2 catalytic inhibitor, indicating that NPD13668 is a potential modulator of EZH2 methyltransferase activity. Our data demonstrated that targeting the pharmacological inhibition of EZH2 activity by NPD13668 might be a novel cancer treatment.